Implementation of Independent Curriculum Differentiation Learning in Physics Learning in High School Completed with Literature Review and Bibliometric Analysis - Putra, Handika Tusuka; Haj, Febri Syahrul; Rizaldi, Dimas Fahmi; Shinta, Chamila El; Deta, Utama Alan; Suliyanah, S.; Admoko, Setyo (Universitas Pendidikan Indonesia (UPI), 2024)
The Independent Learning Curriculum is a new curriculum introduced in Indonesia to restore learning during the pandemic. This research aims to analyze the implementation of independent curriculum differentiation learning at Hang Tuah 5 High School Sidoarjo as the final result of the Field School. Field Introduction Activities (PLP) courses taken for student education programs. This research used an observation method for 16 weeks, and interviews were also conducted aimed at various respondents, and related to the implementation of independent curriculum in schools. The result of this research is the implementation of an independent curriculum. influences many aspects of the field of education. The Independent Curriculum has been implemented at all grade levels, starting from the EX stage to the FXI and FXII stages as a reference for the learning activity process. The implementation of the independent curriculum at Hang Tuah 5 Sidoarjo High School is going well and is supported by various facilities that support good learning at all school levels. The implementation of the Pancasila Student Strengthening Profile is going well, the implementation of learning prioritizes the development of student abilities and is following the environmental conditions around the school.